Cocoa olein glycerolysis with lipase Candida antarctica in a solvent free system - L. S. Zamorano; P. Calero Magaña; E. García Cisneros; A. V. Martínez; L. F. Martín (Grasas y Aceites, 2020)
In this paper we present the valorization of cocoa olein obtained from the acid fat-splitting of soapstocks. The aim is to develop a solvent free process (enzymatically catalyzed) to maximize the production of a final product with high content of monoglycerides (MAG) and diglycerides (DAG). The effect of the enzyme dose, glycerol content, reaction times as well as the modification of the raw material and pressure were studied. The yield of the reaction increased up to 90-95% when using a vacuum of 2-3 mbar at 65 °C, enough to evaporate the water which is generated as a by-product, an enzyme dose of 1% and molar ratio oil:glycerol of 1:2. The highest yield in terms of MAG and DAG production was obtained by starting from a raw material which was rich in free acidity (FFA), rendering oil with 33.4 and 44.2% MAG and DAG, respectively. Short reaction times (6-8 h) were observed compared to previously reported results (24 h).